EMOTIONAL INTELLIGENCE OF PRIMARY SCHOOL TEACHERS - Kotyk, Tetiana (Mountain School of Ukrainian Carpaty, 2020)
The reorientation of the modern Ukrainian school from knowledge to competence is aimed at forming in students’ life experience, necessary knowledge, skills and values important for successful implementation in a rapidly changing society. The concept of the New Ukrainian School proclaims personality-oriented learning, which is focused not on the usual acquisition of knowledge, but on the formation of the child's personality, his character, and attitude to the world. The purpose of modernizing the education system is to transfer the vector of knowledge from the external world of the child, created by nature and man, to master the processes of interaction with this world, understanding the meanings of their own activities. Therefore, the scientific substantiation of the process of preparing teachers for the implementation of the tasks of intelligence, becomes especially relevant. The article reveals the essence of emotional intelligence as a psychological and pedagogical phenomenon, the requirements for emotional intelligence of primary school teachers and the peculiarities of its development in modern teachers. Different definitions of the concept of "emotional intelligence" are highlighted and its essence and structure are generalized in accordance with the professional activity of a primary school teacher, the emotional components of professional competencies of a primary school teacher are determined. The results of the analysis of the professional standard "Primary school teacher of general secondary education" and the Standard educational program for professional development of teachers in self-education of teachers for the development of emotional intelligence of teachers are presented. It was concluded that the obligatory work function of a teacher is the need to self-assess and identify the strengths and weaknesses of their own pedagogical activities, including its emotional component. the New Ukrainian School, in particular in the aspect of the development of such a personal quality of students as emotional intelligence, becomes especially relevant. The article reveals the essence of emotional intelligence as a psychological and pedagogical phenomenon, the requirements for emotional intelligence of primary school teachers and the peculiarities of its development in modern teachers. Different definitions of the concept of "emotional intelligence" are highlighted and its essence and structure are generalized in accordance with the professional activity of a primary school teacher, the emotional components of professional competencies of a primary school teacher are determined. The results of the analysis of the professional standard "Primary school teacher of general secondary education" and the Standard educational program for professional development of teachers in self-education of teachers for the development of emotional intelligence of teachers are presented. It was concluded that the obligatory work function of a teacher is the need to self-assess and identify the strengths and weaknesses of their own pedagogical activities, including its emotional component.